2016
DOI: 10.1186/s12889-016-2881-8
|View full text |Cite
|
Sign up to set email alerts
|

The Gutenberg health study: associations between occupational and private stress factors and work-privacy conflict

Abstract: BackgroundWork-privacy conflict (WPC) is no longer a rarity but constitutes a societal problem. The objectives of the present study were (1) to investigate the distribution and prevalence of WPC among the employed participants in the Gutenberg Health Study at baseline and (2) to study the dependence of WPC on a broad range of private life and occupational characteristics as well as on psychosocial working conditions.MethodsThis analysis is based on a representative, population-based sample of 3,709 employees p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 41 publications
4
32
0
1
Order By: Relevance
“…Work conducted in the past century following up individual subjects (i.e. the Whitehall II study [37]) strongly suggested a possible link between adverse psychosocial work conditions and sickness absence [38][39][40]. Many companies now use employee assistance programs to support individuals with mental challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Work conducted in the past century following up individual subjects (i.e. the Whitehall II study [37]) strongly suggested a possible link between adverse psychosocial work conditions and sickness absence [38][39][40]. Many companies now use employee assistance programs to support individuals with mental challenges.…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of this study, its subscale WPC (46,47) with 7 items from the German version of the COPSOQ was used. The WPC has been associated with overall demands at work, speci cally with cognitive and emotional demands and has been previously shown to be associated with depression (14). The scale has very good internal consistency (Cronbach's alpha= 0.92; 49).…”
Section: Methodsmentioning
confidence: 97%
“…A growing body of research has investigated possible negative consequences of this spill-over, such as higher prevalence of burnout, depression, anxiety, and absenteeism from work as well as lower life satisfaction, lack of energy, sleep disorders, fatigue, and poorer self-reported health (27)(28)(29). In addition, women with depression often reported to have a very high WPC (14) and a 2-year prospective study in Sweden could show that the increased risk of poor self-rated health in uenced by WPC was more pronounced in women than in men (30). In general, mothers and women seem to be at greater risk of WPC (25), especially when holding a university degree or having a high socio-economic status (14).…”
Section: Psychosocial Work Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been evidence that maternal work participation in general has a positive influence on female health (11,12). However, certain aspects of work seem to increase the risk for depression, such as effort-reward imbalance (13) and work-privacy conflict, especially in women outside from the peripartum period (14,15). This leads to the question, how much of an impact job and work-related factors during the prepartum period may have regarding peripartum mental health, especially PPD.…”
Section: Introductionmentioning
confidence: 99%